RANCANG BANGUN SISTEM INFORMASI AKUNTANSI PEMBELIAN BAHAN BAKU SECARA KREDIT - Windy Astuti, Renita; Fauziah, Sifa; tira, Yudhis; Noviriandini, Astrid (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Purchasing Raw Materials is a major factor supporting the smooth production process for garment companies. So that every company must have a good raw material purchasing system to prevent delays in raw material stock for the company’s operations. PT Bintang Anugrah Busana is a company engaged in the garment. The process of purchasing raw materials at PT Bintang Anugrah Busana is not computerized so that the stock is inaccurate, often orders wrong raw materials, information retrieval takes a long time and document security is not guaranteed. Data collection methods used in this study are direct observation methods, interview methods and literature studies. The purpose of this study is to build a design for accounting information systems for purchasing raw materials at PT Bintang Anugrah using a desktop-based programming language Visual Basic 6.0, SQL Server 2014 Express Edition database and for reports supported by Crystal Report with the waterfall model software development method to solve various problems in PT Bintang Anugrah Busana about purchasing raw materials will make stock more accurate, order errors can be minimized, information retrieval is faster and document security is guaranteed.